2014
DOI: 10.1534/genetics.114.163188
|View full text |Cite
|
Sign up to set email alerts
|

Budding Yeast for Budding Geneticists: A Primer on the Saccharomyces cerevisiae Model System

Abstract: The budding yeast Saccharomyces cerevisiae is a powerful model organism for studying fundamental aspects of eukaryotic cell biology. This Primer article presents a brief historical perspective on the emergence of this organism as a premier experimental system over the course of the past century. An overview of the central features of the S. cerevisiae genome, including the nature of its genetic elements and general organization, is also provided. Some of the most common experimental tools and resources availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
163
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(169 citation statements)
references
References 106 publications
0
163
0
6
Order By: Relevance
“…Since then, because of its ease of manipulation and amenability to genetic modifications, yeast has become an extremely powerful model system, to study eukaryotic cell biology (22,23). The development of high-throughput methodologies combined to a high-level of functional conservation from yeast to humans (24,25), has proven especially useful in studying the basic biology that underlies cell functioning and even human diseases (26).…”
Section: Saccharomyces Cerevisiae As An Experimental Model For the Stmentioning
confidence: 99%
“…Since then, because of its ease of manipulation and amenability to genetic modifications, yeast has become an extremely powerful model system, to study eukaryotic cell biology (22,23). The development of high-throughput methodologies combined to a high-level of functional conservation from yeast to humans (24,25), has proven especially useful in studying the basic biology that underlies cell functioning and even human diseases (26).…”
Section: Saccharomyces Cerevisiae As An Experimental Model For the Stmentioning
confidence: 99%
“…The yeast Saccharomyces cerevisiae, baker's yeast, has been very useful for studying ribosome biogenesis as well as other fundamental cellular pathways because the genes and proteins involved are highly conserved with those in more complex organisms (reviewed in Botstein andFink 2011 andDuina et al 2014). Yeast are amenable to a variety of experimental approaches, including genetic, cell biological, and biochemical, all of which the Lycans Laboratory has employed in its investigations.…”
Section: Yeast As a Model Systemmentioning
confidence: 99%
“…Even under controlled process conditions, in which the domesticated yeasts are more prevalent, recent comparative genomic studies have demonstrated cases of spoilage in ethanol plants where native yeast strains were found to indeed overlap those inoculated ones. These wild yeasts can be found in different matrices, from wine making-related environments to tree barks, fruits and even seawater (Duina et al, 2014;Barbosa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%